Aflibercept Biosimilar MYL-1701P vs Reference Aflibercept in Diabetic Macular Edema: The INSIGHT Randomized Clinical Trial - Bressler, Susan B; Barve, Abhijit; Ganapathi, Prasanna C; Beckmann, Katrin; Apte, Rajendra S; Marcus, Dennis M; Baumane, Kristine; Agarwal, Somesh; Oleksy, Piotr; Reichstein, David A; Patel, Sunil S; Ernest, Jan; et al. (JAMA ophthalmology, 2024)
IMPORTANCE: Biosimilars may be lower-cost alternatives to originator biologic products, potentially offering expanded access or reduced economic burden, but have not been evaluated with aflibercept in diabetic macular edema (DME). OBJECTIVE: To compare efficacy and safety of MYL-1701P, an aflibercept biosimilar, with reference aflibercept (Eylea [Regeneron]) in DME. DESIGN, SETTING, AND PARTICIPANTS: This was a double-masked, randomized clinical trial that included participants at 77 centers across the US, Europe, Japan, and India. Included in the analysis were individuals 18 years and older with type 1 or type 2 diabetes with central DME and best-corrected visual acuity (BCVA) letter score of 73 to 38 in the study eye using an Early Treatment Diabetic Retinopathy Study (ETDRS) chart. Study data were analyzed from October to December 2021. INTERVENTIONS: Formulations of MYL-1701P (0.5-mg vial) or reference aflibercept every 4 weeks for 5 consecutive intravitreal injections, followed by every 8 weeks through week 52. MAIN OUTCOMES AND MEASURES: The primary outcome was the adjusted difference in least squares mean (SE) change from baseline BCVA letter score at week 8 with an equivalence margin of -3 to +3 letters. Secondary outcomes included change in central subfield thickness (CST), BCVA, number of injections over 52 weeks, incidence of adverse events (AEs), and antidrug antibodies (ADAs). RESULTS: A total of 355 participants (mean [SD] age, 62.2 [9.2] years; 216 male [60.8%]) were randomized to MYL-1701P (179 participants [50.4%]) and aflibercept (176 participants [49.6%]). At week 8, mean (SE) change in BCVA was 6.60 (0.55) letters vs 6.56 (0.55) letters in the MYL-1701P vs aflibercept groups. The adjusted mean difference of 0.04 letters (90% CI, -1.16 to 1.24 letters) met the primary outcome. At week 8, mean (SE) change in CST was -112 (7) μm vs -124 (7) μm in the MYL-1701P vs aflibercept groups (adjusted mean difference, 12 μm; 90% CI, -3 to 26 μm). The incidence of treatment-emergent AEs in the MYL-1701P and aflibercept arms were ocular (30.9% [55 of 178] vs 29.5% [52 of 176]), serious ocular (0.6% [1 of 178] vs 1.1% [2 of 176]), nonocular (65.2% [116 of 178] vs 65.3% [115 of 176]), and serious nonocular (16.9% [30 of 178] vs 11.9% [21 of 176]). The mean (SD) total number of injections was 8.4 (2.1) vs 8.7 (1.8) in the MYL-1701P vs aflibercept groups. The incidence of treatment-induced or treatment-boosted ADAs was 2.8% (5 of 177) vs 5.7% (10 of 176) in the MYL-1701P vs aflibercept arms. CONCLUSIONS AND RELEVANCE: MYL-1701P demonstrated clinical equivalence in regard to efficacy, with comparable safety and immunogenicity, to reference aflibercept. These findings support use of MLY-1701P as an alternative to reference aflibercept. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT03610646.
Keywords: Male; Treatment Outcome; lidé středního věku; Tomography, Optical Coherence; Receptors, Vascular Endothelial Growth Factor; Diabetic Retinopathy; diabetická retinopatie; Intravitreal Injections; Humans; biosimilární léčivé přípravky; injekce intravitreální; Middle Aged; senioři; zraková ostrost; mužské pohlaví; Female; Vascular Endothelial Growth Factor A; optická koherentní tomografie; Aged; makulární edém; ženské pohlaví; Angiogenesis Inhibitors; rekombinantní fúzní proteiny; Double-Blind Method; Visual Acuity; Macular Edema; Recombinant Fusion Proteins; inhibitory angiogeneze; Biosimilar Pharmaceuticals; lidé; vaskulární endoteliální růstový faktor A; dvojitá slepá metoda; receptory vaskulárního endoteliálního růstového faktoru; výsledek terapie